Investigation of multifaceted asymmetric radiation from the edge (MARFE) with impurity injection from the upper divertor on the Experimental Advanced Superconducting Tokamak. (28th May 2020) - Luo, Yu; Ding, Fang; Wang, Liang; Duan, Yanmin; Ming, Tingfeng; Mao, Songtao; Wang, Yumin; Chen, Xiahua; Li, Kedong; Ye, Dawei; Meng, Lingyi; Xu, Jichan; et al.
Abstract: The phenomenon of multifaceted asymmetric radiation from the edge (MARFE) is investigated with impurity gas puff from the upper divertor on the Experimental Advanced Superconducting Tokamak (EAST). A typical process in which dense radiation region in the vicinity of the X point (X-point MARFE) further evolves into MARFE on the high field side (wall MARFE) after the plasma makes a transition from H-mode to L-mode confinement is observed in discharges with the impurity gas seeding. The electron density distribution and evolution in the divertor volume are measured by means of spectroscopy. It is observed in the experiments that the final position of MARFE is related to the ion ∇ B drift direction. After the phase difference of n = 1 resonant magnetic perturbation (RMP) change from 90° to 270°, MARFE begins to appear on the high field side, which may be caused by the density pump-out induced by RMP. At the same heating power, the density threshold for MARFE formation is somewhat higher in the Ne seeding discharge than in the Ar seeding discharge. This may be attributed to the fact that the divertor radiation fraction, P rad, div / P rad, main, in the Ne seeding discharge is lower than that in the Ar seeding discharge. In addition, MARFE is successfully suppressed by total radiated energy feedback control in radiative divertor experiments. Therefore, radiation feedback control may play a vital role in avoiding major disruption induced by impurity radiation in radiative divertor experiments.